Principles of applied reservoir simulation - Fanchi, John R. (Amsterdam : Gulf Professional Pub., 2006)
SHORT BLURB/BRIEF DESCRIPTION: The hottest, most important topic to reservoir engineers is reservoir simulation. Reservoir simulations are literally pictures of what a reservoir of oil or gas looks, or should look, like under the surface of the earth. A multitude of tools is available to the engineer to generate these pictures, and, essentially, the more accurate the picture, the easier the engineer can get the product out of the ground, and, thus, the more profitable the well will be. UNIQUE FEATURE: Completely revised and updated throughout, this new edition of a GPP industry standard has completely new sections on coalbed methane, CO2 sequestration (important for environmental concerns), Co2 Flood, more sophisticated petrophysical models for geoscientists, examples of subsidence, additional geomechanical calculations, and much more. What makes this book so different and valuable to the engineer is the accompanying software, used by reservoir engineers all over the world every day. The new software, IFLO (replacing WINB4D, in previous editions), is a simulator that the engineer can easily install in a Windows operating environment. IFLO generates simulations of how the well can be tapped and feeds this to the engineer in dynamic 3D perspective. This completely new software is much more functional, with better graphics and more scenarios from which the engineer can generate simulations. BENEFIT TO THE READER: This book and software helps the reservoir engineer do his or her job on a daily basis, better, more economically, and more efficiently. Without simulations, the reservoir engineer would not be able to do his or her job at all, and the technology available in this product is far superior to most companies internal simulation software. It is also much less expensive ($89.95 versus hundreds or even thousands of dollars) than off-the-shelf packages available from independent software companies servicing the oil and gas industry. It is, however, just as, or more accurate than these overpriced competitors, having been created by a high-profile industry expert and having been used by engineers in the real world with successful and profitable results. * This reference is THE industry standard to successfuly modelling reservoirs, obtaining maximum supply and profiting from oil and gas reservoirs * Includes dowloadable software of the new IFLO reservoir simulation software, that can save your company thousands of dollars * This edition has been updated to included new sections on environmentally important issues such as CO2 sequestration, coalbed methane, Co2 Flood * The third edition also provides more sophisticated petrophysical models, examples of subsidence and additional geomechanical calculations.
Introduction to reservoir management -- Basic reservoir analysis -- Multiphase flow concepts -- Fluid displacement -- Frontal stability -- Pattern floods -- Recovery of subsurface resources -- Economics and the environment -- Multiphase fluid flow equations -- Fundamentals of reservoir simulation -- Overview of the modeling process -- Conceptual reservoir scales -- Flow units -- Rock properties -- Distributing rock properties -- Fluid properties -- Model initialization -- History matching -- Predictions -- Introduction to IFLO -- Initialization data -- Recurrent data.
Includes bibliographical references (p. 470-499) and index.
Keywords: Oil fields -- Computer simulation; Electronic books